2015
DOI: 10.1158/1078-0432.ccr-14-0666
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells Increase in Numbers in Perinecrotic Areas in Human Renal Cancer

Abstract: Purpose: Developing strategies to overcome resistance to sunitinib is a major challenge in human renal cell carcinoma (RCC). We hypothesized that sunitinib-induced tumor necrosis-associated hypoxia could interact with renal cancer stem cells in patients with metastatic RCC.Experimental Design: We studied tissue samples from 7 patients with primary metastatic RCC, before and after sunitinib treatment, and from six xenograft models derived from human RCC. Two xenograft models were responders to sunitinib, the fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 33 publications
1
52
0
2
Order By: Relevance
“…When analyzing human samples of RCC, our team recently demonstrated that sunitinib, a tyrosine kinase inhibitor with antiangiogenic effect, was able to generate resistance to its own therapeutic effect via induced hypoxia in cancer stem cells [52]. In human tumor samples obtained before and after treatment with sunitinib from the same patients with metastatic RCC, we observed that renal cancer stem cells increased in numbers after treatment.…”
Section: What Could Limit Their Use For Preclinical Development Of Anmentioning
confidence: 99%
“…When analyzing human samples of RCC, our team recently demonstrated that sunitinib, a tyrosine kinase inhibitor with antiangiogenic effect, was able to generate resistance to its own therapeutic effect via induced hypoxia in cancer stem cells [52]. In human tumor samples obtained before and after treatment with sunitinib from the same patients with metastatic RCC, we observed that renal cancer stem cells increased in numbers after treatment.…”
Section: What Could Limit Their Use For Preclinical Development Of Anmentioning
confidence: 99%
“…rales fondés sur l'implantation de biopsies de tumeurs mammaires ou rénales résistantes ou sensibles aux agents anti-angiogéniques, dans une souris athymique [23,24]. Dans ces modèles, une stabilité histologique et moléculaire par rapport à la tumeur d'origine peut être observée [45] et la stabilité vis-à-vis de la réponse aux traitements antiangiogéniques est également retrouvée.…”
Section: Référencesunclassified
“…La microdissection de cellules endothéliales réalisée à partir de biopsies de métastases, confirme ces observations [24]. Nous avons montré que les modèles expérimentaux précliniques que nous avons développés sont pertinents car la plupart des tumeurs aptes à se développer dans la souris athymique sont les clones les plus agressifs [23,24,45,49]. La possibilité d'identifier différents marqueurs, notamment au niveau des niches de précurseurs endothé-liaux, ouvre une voie nouvelle dans la prise en charge des traitements antiangiogéniques.…”
Section: Référencesunclassified
“…Recently, we demonstrated that sunitinib, a tyrosine kinase inhibitor, was able to generate resistance to its own therapeutic effect via induced hypoxia in cancer stem cells [1]. …”
mentioning
confidence: 99%